Human Resources Management Strategies and Teachers’ Job Performance in Public Senior Secondary Schools - Olaifa, Adeseko Sunday; Oyekunle, Taiye Wasiu; Niji-Olawepo, Olaide Abidemi; Adeoye, Moses Adeleke; Olaifa , Ebunlomo Oreoluwa (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Human resources management strategies have played tremendous roles in the attainment of educational goals. The study investigated human resources management strategies and teachers’ job performance in public senior secondary schools in Kwara State. The study adopted a descriptive survey of correlational type. Two research questions and one hypothesis were raised to guide the study. The researcher's instrument was titled Human Resources Management Questionnaire” (HRMSQ) and Teachers’ Job Performance Questionnaire (TJPQ) was used to collect data for the study. Descriptive statistic of frequency counts, percentages, mean and standard deviation was used to analyse demographics and answer the research questions raised. Inferential statistics of Pearson Product Moment Correlation statistics were used to test the formulated research hypotheses. The findings of the study revealed that; staff promotion practices constituted the highest human resources management strategies in senior secondary schools in Kwara State. Teachers’ job performance was high in public senior secondary schools in Kwara State. There was a significant relationship between human resources management strategies and teachers’ job performance in senior secondary schools in Kwara State. It was recommended among others that public senior secondary schools in Kwara State should give special emphasis on improving their human resources management strategies in the areas of teamwork, job definition, employee participation, compensation, career planning and training.